Functional Phosphorylation Sites in the C-Terminal Region of the Multivalent Multifunctional Transcriptional Factor CTCF - Klenova, Elena M. (American Society for Microbiology, 2001)
CTCF is a widely expressed and highly conserved multi-Zn-finger (ZF) nuclear factor. Binding to various CTCF target sites (CTSs) is mediated by combinatorial contributions of different ZFs. Different CTSs mediate distinct CTCF functions in transcriptional regulation, including promoter repression or activation and hormone-responsive gene silencing. In addition, the necessary and sufficient core sequences of diverse enhancer-blocking (insulator) elements, including CpG methylation-sensitive ones, have recently been pinpointed to CTSs. To determine whether a posttranslational modification may modulate CTCF functions, we studied CTCF phosphorylation. We demonstrated that most of the modifications that occur at the carboxy terminus in vivo can be reproduced in vitro with casein kinase II (CKII). Major modification sites map to four serines within the S(604)KKEDS(609)S(610)DS(612)E motif that is highly conserved in vertebrates. Specific mutations of these serines abrogate phosphorylation of CTCF in vivo and CKII-induced phosphorylation in vitro. In addition, we showed that completely preventing phosphorylation by substituting all serines within this site resulted in markedly enhanced repression of the CTS-bearing vertebrate c-myc promoters, but did not alter CTCF nuclear localization or in vitro DNA-binding characteristics assayed with c-myc CTSs. Moreover, these substitutions manifested a profound effect on negative cell growth regulation by wild-type CTCF. CKII may thus be responsible for attenuation of CTCF activity, either acting on its own or by providing the signal for phosphorylation by other kinases and for CTCF-interacting protein partners.